THE PRINCIPAL ROLE IN IMPROVING STUDENT LEARNING ACHIEVEMENT AT SMPN 01 CIBINONG OF BOGOR DISTRICT - Muh. Takdir (JELLi Journal, 2021)
The objective of this research is to determine the role principal leadership in improving student achievement as an indicator of school quality. This research was conducted at SMPN 01 Cibinong, Bogor district for three months. This research method uses a qualitative approach with descriptive analysis. In collecting data this research used interview, observation and documentation. The data obtained was analyzed through data reduction, data display and conclusion drawing / verification. The conclusion of the study is the ability of the principal to implement the roles as educator, manager, administrator, supervisor, leader, innovator and motivator give the positive impact to improve student achievement and high public interest in advancing the learning process at school.